2006
DOI: 10.1182/blood.v108.11.210.210
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of 2-Weekly CHOP with Rituximab for Aggressive B-Cell Non-Hodgkin’s Lymphoma in Elderly Patients.

Abstract: Treatment results in elderly patients (> 65 yrs) with aggressive Non-Hodgkin lymphoma (NHL) are associated with a lower complete response (CR) rate and a worse survival (OS). Efforts have been made to improve the outcome by adding Rituximab to standard CHOP chemotherapy or by intensifying CHOP from 21 days to 14 days intervals (2-weekly CHOP, CHOP14). The Dutch HOVON and the Scandinavian Nordic groups have performed a prospective, multi-center, randomized phase III trial to compare 8 cycles of CHOP14 chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To improve the prognostic risk assessment in elderly patients treated with R‐CHOP, the age cut‐off in IPI was increased to 70 years to develop E‐IPI . This cut‐off point was based on two large phase 3 trials, RICOVER‐60 and Dutch HOVON, which demonstrated inferior outcomes in patients aged >70 years, compared to patients aged 60–70 years . E‐IPI placed more patients in the low‐risk category compared to the original IPI, and could separate low‐ and low‐intermediate risk groups, which is not possible with R‐IPI in elderly population .…”
Section: Discussionmentioning
confidence: 99%
“…To improve the prognostic risk assessment in elderly patients treated with R‐CHOP, the age cut‐off in IPI was increased to 70 years to develop E‐IPI . This cut‐off point was based on two large phase 3 trials, RICOVER‐60 and Dutch HOVON, which demonstrated inferior outcomes in patients aged >70 years, compared to patients aged 60–70 years . E‐IPI placed more patients in the low‐risk category compared to the original IPI, and could separate low‐ and low‐intermediate risk groups, which is not possible with R‐IPI in elderly population .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of rituximab was associated with a rise in the CR rate from 63% to 75% (Coiffier et al , 2002), a rise in the 5‐year progression‐free survival (PFS) from 30% to 54% ( P = 0·00001) and a rise in the 5‐year OS from 45% to 58% ( P = 0·0073) (Feugier et al , 2005). Since then, a number of further studies have confirmed the efficacy of the addition of rituximab to CHOP in elderly patients with DLBCL (Habermann et al , 2006; Sonneveld et al , 2006; Pfreundschuh et al , 2008). The use of rituximab is highly cost‐effective and a recent study emphasizes that this is particularly true in elderly patients (Johnston et al , 2010).…”
Section: Managementmentioning
confidence: 97%
“…Results from the RICOVER‐60 trial and the Dutch HOVON (Stichting Hemato‐Oncologie voor Volwassenen Nederland) trials in patients over age 60 found age >70 to be an adverse factor (Pfreundschuh et al , 2008; Sonneveld et al , 2006). The latter patients had an inferior outcome largely due to excessive toxicity and the inability to complete the planned therapy.…”
mentioning
confidence: 99%